2020
DOI: 10.1177/0192636520975862
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Standards-Based Learning: Tracking High School Students’ Transition to the University

Abstract: This study sought to determine if the implementation of standards-based learning in high schools affects students’ transition to learning in university courses. Surveys and interviews with 13 students who had graduated from high schools implementing standards-based learning and who had completed their first academic semester at a midsize, private, Midwest university revealed no detrimental effects. The most frequently mentioned transition difficulties related to social issues and time management. Implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…This is especially true of efforts to implement standards-based approaches, either before or after the COVID-19 pandemic. Not only do programs differ drastically from one district or school to the next, but success is sometimes hard to define (see Guskey et al, 2020). Still much can be learned from those districts and schools that tried and, by all accounts, failed.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true of efforts to implement standards-based approaches, either before or after the COVID-19 pandemic. Not only do programs differ drastically from one district or school to the next, but success is sometimes hard to define (see Guskey et al, 2020). Still much can be learned from those districts and schools that tried and, by all accounts, failed.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el legislador español considera que la LOMCE rompió el equilibrio que existía en las competencias de curriculares de la administración central gracias a las leyes que le precedieron, además de recibir mucha oposición. Esto conllevó a que muchas de las medidas propuestas nunca se aplicaran, por lo tanto, se hace propicia la ocasión para aprovechar y tratar de enmendar algunos aspectos con cara a poder afrontar el desafío propuesto por la Unión Europea y la UNESCO para la década 2020-2030(LOMLOE, 2020.…”
Section: La Formación Inicial Del Profesorado En La Normativa Legal V...unclassified
“…En la actualidad hay una gran cantidad de investigaciones sobre la cuestión docente, y con sus resultados han propiciado que, en Europa, volviera a ser centro de debate educativo el profesorado. Lo que ha motivado a que los docentes sean el foco de los debates es el hecho de que Guskey et al (2020), Gutiérrez et al (2016, Tarja y Stefan, (2021); entre otros, han demostrado que, de manera general, la actuación y desempeño de los docentes, tienen gran influencia en la calidad de la educación, y de manera más concreta, es una variable importante en el aprendizaje y éxito académico de los alumnos(as) (Hervis, 2018).…”
Section: La Competencia Digital De Los Docentesunclassified
“…Peters, et al (2017) also found that students and parents worried that standards-based grading will harm students' chances of being accepted into college; yet, these concerns were largely based on an inaccurate understanding of college admissions and college courses. In their study conducted as a response to resistance against standards-based grading, Guskey, et al (2020) found that standards-based learning did not have a detrimental effect on students' transition from high school to college.…”
Section: School Cultures and Traditions Can Be Barriers To Grading Re...mentioning
confidence: 98%